2022
DOI: 10.3409/fb_70-4.24
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure to a Glyphosate-Based Herbicide on Haematological Parameters, Plasma Biochemical Indices and the Microstructure of Selected Organs of the Common Carp ( Cyprinus carpio Linnaeus, 1758)

Abstract: Contamination of water environments with herbicides is a common problem nowadays. The aim of the current study was to evaluate the effects of Roundup on common carp ( Cyprinus carpio) after 1, 3 and 10 days of exposure. The used concentrations corresponded to 1 and 5 mg/l of the active ingredient (glyphosate potassium salt). The haematological analysis performed showed a decrease of the RBC count, as well as an increase of the other erythrocyte indices (Hb, MCV, MCH, MCHC). Most of these changes were dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Moreover, a study investigating the impact of GBH on common carp by exposing them to water concentrations equivalent to 1 and 5 mg/L of glyphosate, found a decrease in RBC count and an increase in in ammation in the exposed carp. The study suggests that hematological parameters are more sensitive and reliable indicators of Roundup exposure in common carp than other tested parameters (Bojarski et al 2022). Another study reported that oral administration of 375 mg/kg of GBH for 56 days induced severe anemia, altered platelets and white blood cells, and caused in ammation and oxidative stress in mice.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, a study investigating the impact of GBH on common carp by exposing them to water concentrations equivalent to 1 and 5 mg/L of glyphosate, found a decrease in RBC count and an increase in in ammation in the exposed carp. The study suggests that hematological parameters are more sensitive and reliable indicators of Roundup exposure in common carp than other tested parameters (Bojarski et al 2022). Another study reported that oral administration of 375 mg/kg of GBH for 56 days induced severe anemia, altered platelets and white blood cells, and caused in ammation and oxidative stress in mice.…”
Section: Discussionmentioning
confidence: 79%
“…In vitro studies indicate that these compounds may cause damage to erythrocytes, inducing oxidative stress, hemolysis, and hemoglobin oxidation (Kwiatkowska et al 2014, Pieniążek et al 2004, Rodrigues et al 2011). Exposure to glyphosate and GBH can lead to decreased red blood cells (RBC) counts, changes in parameters of erythrograms, increased in ammation, and toxic to bone marrow in animal models (Bojarski et al 2022, Mzengereza et al 2020, Prasad et al 2009, Rodrigues et al 2011 Although experimental studies suggest that glyphosate and GBH may have harmful effects on erythrocytes, there is limited understanding of their association with erythrocyte parameters in humans. In an occupational study, a signi cant difference in RBC count was observed among glyphosate-exposed workers compared to non-exposed staff when glyphosate concentration in the air was below 9.40 mg/m³ (Zhang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(Jiraungkoorskul et al, 2002;Ghaffar et al, 2021). Bojarski et al (2022) were observed no histological changes in fish organs. Therefore, hematological parameters were the most reliable and sensitive markers of pesticides exposure of common carp.…”
Section: M3mentioning
confidence: 78%
“…Hematological analysis is one of the tools commonly used to evaluate the health and welfare of fish, both under aquaculture conditions and in scientific studies, to assess the influence of environmental factors on fish [ 1 , 16 ]. The study conducted by Bojarski et al [ 53 ] demonstrated that hematological indices were the most sensitive and reliable biomarkers of exposure of Cyprinus carpio to the herbicide Roundup. Far fewer changes in comparison to hematological ones were observed in the blood biochemical parameters, while microstructure of the analyzed organs (gills, liver, trunk kidney) was unchanged.…”
Section: Hematological Analysis In Fish Toxicologymentioning
confidence: 99%